Hypertension and Salt Consumption: A Story from A Coastal Area - Titik Respati; Zulfi Noor Fadia; Wida Purbaningsih; Fajar A Yulianto; Tri Wahyuni (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2025)
Indonesia has a high prevalence of hypertension accompanied by relatively high salt consumption, posing a significant public health concern, particularly in coastal areas where salty foods and saline water are commonly available. This study aimed to analyze the relationship between salt consumption and hypertension grade among residents in a coastal area. A cross-sectional study was conducted involving 174 hypertensive patients in Pangandaran District who had recorded blood pressure measurements at the local health center. Data on respondents’ characteristics, including age, sex, education level, occupation, and income, were collected. Salt intake was assessed using a Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ). Multiple logistic regression analysis was performed to examine the association between salt consumption and hypertension grade while controlling for potential confounding variables. The mean sodium intake among respondents was 1312.11 ± 596.27 mg/day. Salt consumption was significantly associated with hypertension grade (β = 0.001; p = 0.004) after adjustment for education level and type of occupation. In conclusion, higher salt consumption is significantly associated with increased severity of hypertension in coastal populations, highlighting the need for targeted dietary interventions to reduce salt intake in these areas.